AFGE LOCAL 1812 NORMAN PAINTER-MIRIAM SZAPIRO - ROBERTSON G (Tufts Archival Research Center, 2007)
Missing Attachments; Letter to Susan Stuntz from Gray Robertson introducing (missing) proposal to American Federation of Government Employees Local Union 1812. Announces fees for requested studies.